2013
DOI: 10.1080/00380768.2013.789397
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus compounds and their solubility in swine manure compost

Abstract: Swine manure compost (SMC) contains a significant amount of phosphorus (P). In this study, the characteristics of P compounds in SMC were investigated by the nondestructive X-ray diffraction (XRD) method, chemical extraction, and a cultivation experiment. Only magnesium ammonium phosphate hexahydrate (MAP or struvite, MgNH 4 PO 4 ·6H 2 O) was detected as crystal P compound by XRD in most SMC. Furthermore, MAP crystal was observed by scanning electron microscope (SEM) image. The amount of ammonium nitrogen in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Contrasting, >50% of P t in cattle manure were easily extractable and identified mainly as inorganic phosphates by 31 P-NMR [57]. They extracted only small amounts of P by HCl, interpreted as less available Ca-bound P. The resulting predominance of rather easily available orthophosphates was confirmed by others, who additionally detected magnesium ammonium phosphate hexahydrate by X-ray diffraction analysis [58,59]. However, pyrolysis reduced the extractability of P compared to that in the source manure, for example, due to the conversion into less-soluble whitlockite [60] and HA [61].…”
Section: Discussionmentioning
confidence: 81%
“…Contrasting, >50% of P t in cattle manure were easily extractable and identified mainly as inorganic phosphates by 31 P-NMR [57]. They extracted only small amounts of P by HCl, interpreted as less available Ca-bound P. The resulting predominance of rather easily available orthophosphates was confirmed by others, who additionally detected magnesium ammonium phosphate hexahydrate by X-ray diffraction analysis [58,59]. However, pyrolysis reduced the extractability of P compared to that in the source manure, for example, due to the conversion into less-soluble whitlockite [60] and HA [61].…”
Section: Discussionmentioning
confidence: 81%
“…The HClsoluble P in animal manure compost, which is assumed to be calcium phosphate with a high calcium (Ca)/P ratio, is estimated to be very low in solubility to water and bioavailability for a short period. Komiyama et al (2013) demonstrated that the acid-soluble P with low water solubility in manure compost was not available for Japanese mustard spinach (Komatsuna; Brassica rapa L. var. perviridis) by the cultivation experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately three-quarters of the P absorbed by rice plants is transferred to rice grain, and used as food for humans or feedstuff for animal production. The P 2 O 5 concentration in chicken manure and swine manure is as high as 5-6% on a dry-weight basis (Komiyama et al 2013). The major constituent form of P is MgNH 4 PO 4 Á6H 2 O (see Sect.…”
Section: P Cycle In Irrigated Lowland Paddy Field Soilmentioning
confidence: 99%